Purification characteristics and parameters optimization of anthocyanin extracted from blueberry - Zheng, Xianzhe; Zhang, Zhaoguo; Jin, Changjiang; Mu, Yanqiu; Liu, Chenghai; Chen, Zhiying; Liu, Haijun; Lin, Zhen (International Journal of Agricultural and Biological Engineering, 2015)
To improve the yield and purity of anthocyanin extracted from blueberry, the characteristics and optimization for the separation and purification process of anthocyanin by AB-8 macroporous adsorbent resin was studied. In the absorption stage, the pH value has positive effect in ranges of 1.0-3.0 and the temperature rise has firstly negative then positive effect on adsorption rate of anthocyanin with adsorption time. In the desorption stage, the ethanol concentration increase has firstly positive then steady effect and the temperature rise has positive and then negative effect on desorption rate of anthocyanin. The purification temperature may improve diffusion or induce degradation of anthocyanin. AB-8 macroporous adsorbent resin is suitable to purify the anthocyanin from extract of powdered blueberries and the optimum parameters were obtained by using Design Expert software as adsorption time of 3 h, pH value of 1.0, adsorption temperature of 18°C in absorption stage and desorption time of 30 min, ethanol concentration of 46.5%, desorption temperature of 22°C in desorption stage with the highest absorption rate and desorption rate are 87.65% and 84.80%, respectively.Keywords: parameters optimization, extraction, purification, adsorption, desorption, anthocyanin, blueberryDOI: 10.3965/j.ijabe.20150802.1407